The Quest for Reading: A Reception and Aesthetic Response Criticism on Hypertext Fiction of Pride and Prejudice - Ida Rochani Adi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
The development of internet which provides hypertext information results in significant change in many aspects of life. Literature is not exceptional. The argument is therefore, since hypertext literature is presented in different mode, it must propose different kind of reading. Based on reception and reader-response or aesthetic response theories, this study finds out that there is a change in the way readers enjoy Pride and Prejudice. The process of reading become active experience because it allows the readers to take control of the narrative. The result is that hypertext Pride and Prejudice provides different meaning to the readers. The novel exists by providing not only the narratives but also informations on the narratives. The study finds out that there is a change in how the hypertext Pride and Prejudice wanted and needed. The hypertext does not come from the enjoyment in the process of reading the narratives but the satisfaction in getting the information on the narratives. It is not reading for pleasure that is traditionally offered by romantic novels but the satisfaction in the process of getting information on the text since self actualization in the readers is fulfilled.